2021
DOI: 10.3390/ani11051286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on Gut-Microbial Metabolites, Gastrointestinal Peptides, Glycolipid Metabolism, and Performance of Broilers

Abstract: This paper investigated the effects of heat stress on gut-microbial metabolites, gastrointestinal peptides, glycolipid metabolism, and performance of broilers. Thus, 132 male Arbor Acres broilers, 28-days-old, were randomly distributed to undergo two treatments: thermoneutral control (TC, 21 °C) and high temperature (HT, 31 °C). The results showed that the average daily gain (ADG), average daily feed intake (ADFI), and gastric inhibitory polypeptide (GIP) concentration in the jejunum significantly decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…Furthermore, all the relevant data reported were cross-checked with the literature and showed no discrepancies in the current study. For example, the recorded growth performances of Arbor Acres in this study were concordant to recently published articles [59,60]. In addition, the average BWs obtained after hatch (45.1 g), 7 days (165.7 g), 21 days (981.1 g), and 28 days (1624.1 g) were in line with the Arbor Acres broiler performances (as-hatched performance) objective, which recommends 43 g, 204 g, 978 g, and 1567 g for the same periods, respectively [61].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, all the relevant data reported were cross-checked with the literature and showed no discrepancies in the current study. For example, the recorded growth performances of Arbor Acres in this study were concordant to recently published articles [59,60]. In addition, the average BWs obtained after hatch (45.1 g), 7 days (165.7 g), 21 days (981.1 g), and 28 days (1624.1 g) were in line with the Arbor Acres broiler performances (as-hatched performance) objective, which recommends 43 g, 204 g, 978 g, and 1567 g for the same periods, respectively [61].…”
Section: Discussionsupporting
confidence: 91%
“…At the family level, the proportions of Christensenellaceae, Clostridiaceae, and Erysipelotrichaceae increased; these bacteria were reported to be beneficial to normal glucose metabolism, alleviate insulin resistance, and lower the risk of obesity [ 30 , 31 ]. Our previous study showed that the abundance of Christensenellaceae was significantly reduced by heat stress, while the abundance of Christensenellaceae was significantly increased in the 0.4 mg/kg supplemented group [ 8 ], indicating that glucose metabolism in the chromium supplement group improved. At the genus level, the proportion of Ruminococcus decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The gut releases hormones to regulate glucose metabolism and balance glucose homeostasis when feeding. Our previous research indicated that high temperature significantly affects the levels of CCK, ghrelin, and GIP [ 8 ]. In the current study, the results showed that 0.4 mg/kg Cr as supplemented Cr-Pic decreased the levels of CCK in the jejunum and circulation, increasing the GIP level in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations